Non-invasive control of protein-surface interactions for repeated electrochemical immunosensor use - Khoo, M.M.; Rahim, Z.; Darwish, N.T.; Alias, Y.; Khor, S.M. (2016)
Although most immunosensors which have high affinity antigen-antibody interactions can perform highly specific and sensitive detection, antibody-antigen bonds are typically too strong to allow for rapid reversibility. Therefore, creating a biosensor platform capable of non-invasive surface regeneration is important for reducing costs and being able to perform multiple measurements without losing sensor sensitivity. A reusable electrochemical immunosensor was developed on which a glassy carbon plate was passivated with a mixed layer of 4-nitroaniline/p-phenylenediamine, attached with gold nanoparticles, followed by surface-bound epitope (sulfo-NHS-biotin) to which the monoclonal anti-biotin IgG antibody was complexed. Free biotin was detected when the antibody dissociated from the surface-bound epitope in the presence of free biotin during a displacement assay. The electrochemical impedance spectroscopy technique was used to monitor the protein-surface interactions. To ensure that the immunosensor could be used repeatedly, electrode polarization was used to remove as much surface-bound antibody as possible by applying a negative potential to the working electrode. Therefore, the antibody could bind to the surface-bound epitope again after the electrode was reincubated in the antibody solution, and hence, the displacement assay could be performed again for repeated sensor use. Comparisons between disposable and reusable biosensors are discussed in this paper.